Exploring the behavior of Candida antarctica lipase B in aqueous mixtures of an imidazolium ionic liquid and its surfactant analogue - Campodónico, Paola R.; Calderón, Cristian; Alcázar, Jackson J.; Olivares, Belén; Jaldin, Limberg; Suárez-Rozas, Cristian (Frontiers in Chemistry, 2024)
The performance of Candida antarctica lipase B (CALB) has been evaluated in 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4)/water mixtures in a wide range of molar fractions (χBMIMBF4) with and without 1-dodecyl-3-methylimidazolium tetrafluoroborate (C12-MIMBF4), a surfactant derived from BMIMBF4. The main aim of this work is to evaluate the influence of χBMIMBF4 over micellar aggregates to assess the activity of enzymatic reactions. The investigated reaction corresponds to the hydrolysis of the substrate p-nitrophenyl laureate in each χBMIMBF4. The kinetic study for χBMIMBF4 at around 0.2 proved to be a border point in enzymatic activity. At χBMIMBF4 = 0.1, the lipase activity increases in the presence of C12-MIMBF4. However, at higher concentrations, BMIMBF4 has a negligible effect over the lipase activity. These results suggest specific interactions between water and BMIMBF4 molecules in relation to CALB. This research highlights the superactivity phenomenon driven by the reaction media and the micelle interface. In this interfacial interaction, BMIMBF4 acts directly on the changes induced on the enzyme upon its interaction with the micellar interface. This study opens a green perspective toward the biocatalysis field.